DIGITALISASI UKM DALAM ILMU HUBUNGAN INTERNASIONAL: STUDI KASUS TIONGKOK - Savitri Nurlia Devi (Jurnal Sentris, 2019)
Globalization has affected a lot of sector in international relations such as actor, including Small Medium Enterprises (SMEs). SMEs comes from every country, and SMEs has huge impacts on their national economy. SMEs has a huge effect on the number of a country's export. It makes the sustainability of export in a country depending on SMEs as one of the actors. The appearance of globalization become a challenge for every SMEs in any country to survive through globalization. Because in the globalization era, every SMEs have to increase their ability to trade especially in their ability to use the new technology. And if SMEs in a country cannot improve their ability facing globalization, it can be hard for SME to compete their competitor and it can be a disaster for the sustainability of the SMEs and for their countries. China is an example of a country that pushes and helps SMEs to improve their skills and improve their ideas. And because of the SMEs in China, China can increase its ability in international trading. This writing will try to explain how can SMEs become an important actor in international relations, especially in increasing a country power’s in the international system through digitalization.